Zooplankton adrift: investigating transportation by cyclonic eddy. Issue 5 (28th May 2018) - de Lecea, Ander M.; Coppin, Ross; Noyon, Margaux; Huggett, Jenny A.
ABSTRACT: Eddies are important not just because they have momentum and can transfer water properties, but also because they play an important role in increasing the trophic energy available to organisms, thereby enhancing primary productivity. This study was conducted to test the 'suitcase hypothesis' – the inclusion of organic matter (OM), plankton and larvae within the single water mass of an eddy, which are then highly conserved and transported to another location. Here we hypothesize that particulate OM (POM) and zooplankton from the continental shelf of Madagascar become trapped as the eddy forms and are transported westwards. We analysed stable isotope signatures of POM and zooplankton from samples collected from the continental shelf (CS) as well as within an eddy that had recently formed off the south-west coast of Madagascar. There was no statistical difference in the POM isotopic signature or C/N ratios between the continental shelf or any of the eddy regions. However, some C/N ratio values could suggest that some OM from close to the coastal region could have been transported by the eddy. This was not the case for zooplankton, however, with isotopic signatures on the CS greatly differing from those in the eddy. Several factors could account for these differences including feeding behaviour or tissue turnover rate. We conclude that our study did not gather enough evidence to support (or reject) the 'suitcase' hypothesis, and further studies are needed in order to fully understand the transport of material, including zooplankton and larvae, by eddies.